Uma análise da volatilidade do PIB brasileiro - Brandão, Lisandro Meira Lima (2009)
This work analyses the Brazilian output volatility from 1980 to 2008, which exhibits a sharp decline of 70% since the early 1990s. By analyzing the behavior of the variables that constitute the output, its components and determinants, this work seeks to show the reasons of this significant drop in output volatility during the considered period. Low output volatility brings positive consequences for society welfare, for income distribution and for long term growth. Several studies have been written to point out the causes of the decline in output volatility in different countries over the last two decades, a phenomenon that has been called as 'The Great Moderation' in the United States. Considering the benefits of this process, understanding their causes is indispensable for defining economic policies that guarantees the sustainability of moderated economic cycles. This work focuses on the importance of nominal factors (demand shocks) to explain the decline of Brazilian output volatility. On the hand, the absence of external restrictions for economic growth and the last worldwide prosperity cycle represent the contribution of the external portion. On the other hand, better practices of macroeconomic policies respond for the internal causes.